On the evolutionary origins of differences in sexual preferences - Ryabko, Daniil; Reznikova, Zhanna (Frontiers in Psychology, 2015)
A novel general explanation of the evolutionary process leading to the appearance of differences in sexual preferences is proposed. The explanation is fully general: it is not specific to any particular type of sexual preferences, nor to any species or population. It shows how different sexual preferences can appear in any large group-living population in which sexual selection is sufficiently strong in each sex. The main idea is that the lack of interest towards a member of the opposite sex may be interpreted as a signal of popularity, and thus a sign of reproductive success. It is then boosted by the Fisher runaway process, resulting in a generalized trait~--- lack of interest towards the opposite sex. This trait develops far beyond the point when it gives a reproductive disadvantage, resulting in well-pronounced different sexual preferences. This hypothesis is placed into the context of other works on different sexual preferences in animals; supporting evidence from the literature is reviewed and additional research needed to confirm or refute the hypothesis in any given species is outlined.